Restoration of pro-inflammatory cytokines and histopathological changes in pancreas and liver of hyperglycemic rats by Murraya koenigii leaves extract - Fauzul Husna, Franciscus D. Suyatna, Wawaimuli Arozal, Erni H. Purwaningsih, Yulvian Sani (Journal of Applied Pharmaceutical Science, 2020)
This study aims to investigate whether the characteristic of anti-inflammatory and protective effect of hepato- pancreas could mediate the antihyperglycemic effect of Murraya koenigii. Twenty-five Sprague-Dawley rats were induced hyperglycemia by streptozotocin and nicotinamide (STZ-NA). The hyperglycemic rats were treated with an ethanolic extract of M. koenigii 200 mg/kg b.w and 400 mg/kg b.w. One group of the rats was treated with glibenclamide (1 mg/ kg b.w). After M. koenigii extract and glibenclamide for 4 weeks, the rats were sacrificed. Blood and organ samples were collected under a fasting condition. The evaluation was made towards the expression of pro-inflammatory cytokines (TNF-α, IL-1β) as well as the histopathological change in the liver and pancreas. The beneficial effects of Murraya ko enigii would bring the anti-inflammatory and hepatoprotective effect and increased the number and size of islet Langerhans. This research reveals that M. koenigii has a charateristic of anti-inflammatory, hepatoprotective, and it contributes to regeneration of damaged pancreatic islet. This effect is accompanied by a decrease in plasma glucose levels.
Keywords: Anti-inflammatory, histomorphological, hyperglycemia, Murraya koenigii.